Analysis of Employee Job Satisfaction at PT. Sima Sakti Aulia - Nur’arif, Muhammad Irfan; Anggini, Megah Dewi; Karmila, Ila (Journal Of Resource Management, Economics And Business, 2025)
Purpose: This study aims to analyze employee job satisfaction at PT. Sima Sakti Aulia, a company operating in the travel and tourism industry. The research explores the key factors influencing job satisfaction and examines how these elements contribute to both individual and organizational performance. Research Methodology: A qualitative research approach was employed, utilizing interviews and direct observations of an employee. The data collection process provided in-depth insights into various aspects of the work environment, including physical conditions, facilities, interpersonal relationships, and overall employee well-being. The qualitative nature of the research allowed for a comprehensive understanding of the subjective experiences and perceptions of employees. Results: The findings indicate that employee job satisfaction at PT. Sima Sakti Aulia is significantly influenced by a range of factors. A positive work environment, including effective communication and mutual respect among coworkers, plays a critical role in fostering job satisfaction. Additionally, the company’s provision of adequate facilities such as salaries above the minimum wage, health benefits, and incentive programs further enhances employee satisfaction. Furthermore, harmonious relationships among employees, coupled with opportunities for professional growth, contribute to a supportive workplace culture that encourages high levels of engagement and motivation. Limitations: One limitation of this study is the reliance on a single employee interview, which may not fully represent the experiences of all employees within the company. The findings are based on qualitative data, which provides rich insights but may lack generalizability to a larger population. Future research could benefit from a broader sample size and more diverse perspectives from multiple employees within the organization. Contribution: This research contributes to the understanding of employee job satisfaction within the tourism and travel industry, specifically in a company like PT. Sima Sakti Aulia. The study highlights the importance of addressing both physical and psychological factors in creating an optimal work environment. The results emphasize the role of adequate facilities, supportive relationships, and a positive work culture in enhancing employee motivation and organizational success. This study provides valuable insights for businesses aiming to improve employee satisfaction and, ultimately, organizational performance.